Associação entre a adoção do target costing e as características do relacionamento entre empresas adotantes e seus parceiros de negócios - Braga, Eliane Cortes (2022)
Target costing is an artifact of strategic cost management and its implementation by organizations is growing all over the world due to increased competitiveness. In addition, the increased competition made companies assume an external focus in order to maximize their competitive advantage, whose context favored the emergence of interorganizational cost management (ICM) that arises from the commercial relationship between two or more companies. Target costing is the main mechanism of ICM. Thus, this research aimed to investigate how the adoption of target costing is associated with characteristics referents to the relationship between adopting companies and their business partners. The sector chosen for the application of this study was the information and communication technology (ICT) services sector due to its importance for the Brazilian economy. A survey was carried out, using a standardized and structured online questionnaire, with companies associated with ASSESPRO (Associations of Brazilian Information Technology Companies). Data were analyzed using descriptive statistics and the non-parametric Kruskal-Wallis test. The results found show that the characteristics of the investigated companies have a very low influence on the perception of the conceptual aspects of target costing, the adoption of practices related to the target costing process and the characteristics of interorganizational relationships. The characteristics that had the most influence were: billing, number of hierarchical levels and the base of transactions. It was also found that the principles and elements of target costing were the conceptual aspects that most influenced the adoption of target costing practices and also on aspects of the characteristics of interorganizational relationships. In addition to influencing the adoption of target costing process practices, the conceptual aspects, especially the principles and elements, also favor the presence of some aspects of the interorganizational characteristics in the investigated companies, which, in turn, encourage the adoption of practices of the target costing process. Therefore, it is concluded that interorganizational relationships characterized by aspects of interdependence, stability, cooperation, trust and mutual benefits favor the adoption and use of target costing. The frequency of negotiations and relationship time, aspects of stability, and the increase in organizational learning, an aspect of mutual benefits, are those that most influence the adoption of the target costing practice.